Cutting edge advancements in biochar applications: thermochemical, fermentative, photocatalytic and electrocatalytic hydrogen production and storage - Rizwan, Muhammad; Eisa, M. H.; Zada, Amir; Azizi, Shohreh; Alkaoud, Ahmed M.; Albishi, Miqad S.; Chen, Hong (ELSEVIER SCI LTD, 2025)
Environmental pollution and energy issues have grown significant concern recently. To confiscate toxic and hazardous materials from the environment and deal with energy issues properly, smart materials are highly demanded. Biochar-based materials are gaining much attention owing to their porous structures, large number of active sites, and high graphitization characters to deal with environmental pollution and energy issues. In the present review article, we have discussed the characteristics of biochars and their preparation from various sources and wastes. The applications of biochar-based materials for green hydrogen evolution have been elaborated in detail. A comprehensive debate has been offered to demonstrate how biochars boost the adsorption efficiency, extend light absorption, and improve charge separation to assist hydrogen generation. The thermochemical, fermentative, photocatalytic, and electrocatalytic generation of hydrogen with biochar-based composites have been discussed in much detail. The role of biochar in hydrogen storage and various factors which affect the storage capacity of biochar have been discussed. Future perspective and research gap in the utilization of biochars for energy generation has been presented in the last. This review will highlight and attract more research towards the applications of biochar in energy and environmental sectors.
Keywords: Biochar; Biomass; Electrocatalysis; Fermentation; Hydrogen generation; Photocatalysis; ANAEROBIC-DIGESTION; CHARGE SEPARATION; BIOMASS PYROLYSIS; CO2 REDUCTION; ACTIVE-SITES; ADSORPTION; EVOLUTION; CARBON; NANOCOMPOSITES; NANOPARTICLES; Energy & Fuels; Engineering